2021
DOI: 10.1016/j.jsams.2020.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Sport Concussion Assessment Tool: baseline and clinical reference limits for concussion diagnosis and management in elite Rugby Union

Abstract: Three of the authors (RT, EF, MH) are full-time and part-time employed by World Rugby in roles of research and medicine. JP and GF have served as independent advisors on a working group on concussion administered by World Rugby, for which expenses are covered. Ethics approval and consent to participateThe research plan for this study was approved by the World Rugby Institutional Ethics committee (REF 19007). Players had provided written informed consent for all data gathered as part of the World Rugby Concussi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
3
9
0
Order By: Relevance
“…These results are consistent with prior literature in that fatigue is typically the most frequent or second most frequent symptom reported during baseline SCAT evaluations across a variety of age groups, geographic regions, and sports (Schneider et al, 2010;Jinguji et al, 2012;Hänninen et al, 2016;Petit et al, 2020;Tucker et al, 2020b), and difficulty sleeping is also common (Schneider et al, 2010;Jinguji et al, 2012;Hänninen et al, 2016;Tucker et al, 2020b), reflecting that these symptoms occur frequently in daily life (Yengo-Kahn et al, 2016). Scores on the SAC and mBESS were high but imperfect and were broadly consistent with prior normative studies (Jinguji et al, 2012;Valovich McLeod et al, 2012;Snyder et al, 2014;Hänninen et al, 2016;Snedden et al, 2017;Tucker et al, 2020b). Small proportions of the current sample earned perfect scores on SAC delayed recall (8%) and digits backwards (38%), while most of the sample (85%) correctly named the months in reverse.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These results are consistent with prior literature in that fatigue is typically the most frequent or second most frequent symptom reported during baseline SCAT evaluations across a variety of age groups, geographic regions, and sports (Schneider et al, 2010;Jinguji et al, 2012;Hänninen et al, 2016;Petit et al, 2020;Tucker et al, 2020b), and difficulty sleeping is also common (Schneider et al, 2010;Jinguji et al, 2012;Hänninen et al, 2016;Tucker et al, 2020b), reflecting that these symptoms occur frequently in daily life (Yengo-Kahn et al, 2016). Scores on the SAC and mBESS were high but imperfect and were broadly consistent with prior normative studies (Jinguji et al, 2012;Valovich McLeod et al, 2012;Snyder et al, 2014;Hänninen et al, 2016;Snedden et al, 2017;Tucker et al, 2020b). Small proportions of the current sample earned perfect scores on SAC delayed recall (8%) and digits backwards (38%), while most of the sample (85%) correctly named the months in reverse.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the most common symptoms were fatigue or low energy (33%), trouble sleeping (24%), headache (23%), neck pain (22%), and difficulty remembering (21%). These results are consistent with prior literature in that fatigue is typically the most frequent or second most frequent symptom reported during baseline SCAT evaluations across a variety of age groups, geographic regions, and sports (Schneider et al, 2010 ; Jinguji et al, 2012 ; Hänninen et al, 2016 ; Fuller et al, 2018 ; Petit et al, 2020 ; Tucker et al, 2020b ), and difficulty sleeping is also common (Schneider et al, 2010 ; Jinguji et al, 2012 ; Hänninen et al, 2016 ; Fuller et al, 2018 ; Tucker et al, 2020b ), reflecting that these symptoms occur frequently in daily life (Yengo-Kahn et al, 2016 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…30 A large sample of rugby union athletes achieved an average of 21.5 (SD=3.7; median=21) on Immediate Memory and 7.1 (SD=1.9; median=7) on Delayed Recall. 31 All of these studies determined that the ten-word list largely eliminated the ceiling effects found on the five-word lists. Although NHL players had similar scores on the Immediate Memory and Delayed Recall scores, the form differences across the word lists in our sample as well as the differences by language preference preclude the use of an omnibus mean across the entire sample.…”
Section: Discussionmentioning
confidence: 99%